Strength training: importance of genetic factors - Thomis, M. A.; Beunen, G. P.; Maes, H. H.; Blimkie, C. J.; Van Leemputte, M.; Claessens, A. L.; Marchal, G.; Willems, E.; Vlietinck, R. F. (Medicine & Science in Sports & Exercise, 1998)
Abstract Purpose: This study focuses on the quantification of genetic and environmental factors in arm strength after high-resistance strength training. Methods: Male monozygotic (MZ, N = 25) and dizygotic (DZ, N = 16) twins (22.4 ± 3.7 yr) participated in a 10-wk resistance training program for the elbow flexors. The evidence for genotype*training interaction, or association of interinidividual differences in training effects with the genotype, was tested by a two-way ANOVA in the MZ twins and using a bivariate model-fitting approach on pre- and post-training phenotypes in MZ and DZ twins. One repetition maximum (1RM), isometric strength, and concentric and eccentric moments in 110 ° arm flexion at velocities of 30°·s-1, 60 °·s-1, and 120°·s-1 were evaluated as well as arm muscle cross-sectional area (MCSA). Results: Results indicated significant positive training effects for all measures except for maximal eccentric moments. Evidence for genotype*training interaction was found for 1 RM and isometric strength, with MZ intra-pair correlations of 0.46 and 0.30, respectively. Bivariate model-fitting indicated that about 20% of the variation in post-training 1 RM, isometric strength, and concentric moment at 120 °·s-1 was explained by training-specific genetic factors that were independent from genetic factors that explained variation in the pretraining phenotype (30-77%). Conclusions: Genetic correlations between measures of pre- and post-training strength were indicative for high pleiotropic gene action and minor activation of training-specific genes during training.